PENGARUH TAX AVOIDANCE JANGKA PANJANG TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan Manufaktur yang terdaftar di BEI periode 2011-2012) - Ari Putra Permata Simarmata; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
This study aims to examine the influence of long-run tax avoidance on firm’s value with institutional ownership as moderating variable. Variables examined in this research consisted of tax avoidance which measured with cash effective tax rate (CashETR) and for the long-run tax avoidance calculated usingcumulative 10 years, firm value as measured using Tobins’Q, and institutional ownership. The sample which is used in this research was extracted with using purposive sampling method. After reduces with several criteria, 34 firms are determined as samples. The test results showed that short-run tax avoidance effect on long-run tax avoidance, and institutional ownership effect on firm value. Meanwhile, long-run tax-avoidance does not significant effect on firm value and there is not any increase in firm value after a practice of long-run tax avoidance, also variable of institutional ownership can not strengthen the relationship between long-run tax avoidance on firm value.